Comparative efficacy of xylazine-ketamine premedication on propofol anaesthesia for caesarean sectin in dogs - Ranjith Mohan M (Department of Veterinery Anatomy and Histology, College of Veterinary and Animal Science, 2006)
A study was conducted to evaluate the comparative efficacy of xylazine and xylazine-ketamine premedication on propofol anaesthesia in twelve female dogs of different breeds subjected to caesarean section at the Veterinary College Hospitals at Mannuthy and Kokkalai. All the dogs were clinically examined and were randomly divided into two group’s viz. Group I and Group II, each consisting of six dogs. They were serially numbered from 1 to 6.